Metaphorical Conceptualization of ANGER, FEAR and SHAME in Lithuanian: In Search of Cultural Content - Bogdzevič, Monika (Vilnius University Open Series, 2021)
The article discusses the conceptual images of ANGER, FEAR and SHAME in Lithuanian. The aim of the paper is to show the cognitive and cultural basis for the perception, valuation and linguistic expression of feelings of anger, fear and shame in Lithuanian. Conceptual metaphors and, in some cases, conceptual metonymies are used to reveal tendencies in thinking about these feelings. To this end, linguistic constructs are used to express various aspects of anger, fear and shame as well as the norms and behaviors associated with them. The research inventory consists of lexemes belonging to the categories of anger, fear and shame, composite linguistic units, which contain these lexemes or which are regularly associated semantically with the said lexemes, as well as derivatives derived from metonymic and metaphorical transfers and phraseological compounds. The structure of the article is measured by the source domains of the conceptual metaphors of ANGER, FEAR and SHAME. On this basis, first of all, the conceptual metaphors of the common source domain, which reveal the common patterns of perception of anger, fear and shame, are discussed (CONTAINER / CLOSED SPACE / UP and DOWN MOVEMENT / BALANCE; HUMAN / COMPANION / ENEMY; ANIMAL / BEAST; ARTEFACT; HEAT (FIRE) / COLD; DISEASE), the following are the directions of linguistic conceptualization specific to individual feelings only (PAIN / SUFFERING; BITTER / POISON; NATURAL FORCES / AIR / DARKNESS; PLANT (TREE / CEREALS); WATER (SEA / RIVER); DEVIL) First one reveal the common cognitive basis of the perception and evaluation of the feelings of ANGER, FEAR and SHAME, the second allows us to see the cultural layer of latter.
Keywords: conceptual metaphors; concept of ANGER; concept of FEAR; concept of SHAME